2006
DOI: 10.1182/blood-2006-05-020495
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous wound healing is impaired in hemophilia B

Abstract: We used a mouse model to test the hypothesis that the time course and histology of wound healing is altered in hemophilia B. Punch biopsies (3 mm) were placed in the skin of normal mice and mice with hemophilia. The size of the wounds was measured daily until the epidermal defect closed. All wounds closed in mice with hemophilia by 12 days, compared with 10 days in normal animals. Skin from the area of the wound was harvested at different time points and examined histologically. Hemophilic animals developed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(153 citation statements)
references
References 59 publications
3
145
1
2
Order By: Relevance
“…Studies on wound healing in hemophilia B mice (FIX -/-) showed that macrophage infiltration and wound healing were delayed, potentially because of insufficient thrombin-mediated generation of fibrin degradation-based chemoattractant agents and insufficient fibrin scaffolding for reepithelialization of the wound area (20). Other studies have demonstrated that in FXIII -/-mice, a delay in reepithelialization of the wounded area occurs that is rescued with FXIII treatment (21).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on wound healing in hemophilia B mice (FIX -/-) showed that macrophage infiltration and wound healing were delayed, potentially because of insufficient thrombin-mediated generation of fibrin degradation-based chemoattractant agents and insufficient fibrin scaffolding for reepithelialization of the wound area (20). Other studies have demonstrated that in FXIII -/-mice, a delay in reepithelialization of the wounded area occurs that is rescued with FXIII treatment (21).…”
Section: Introductionmentioning
confidence: 99%
“…The haemophilic mice exhibit delayed cutaneous wound closure with abnormal histology, including: (i) subcutaneous haematoma formation near the wound site; (ii) delayed macrophage influx; (iii) delayed reepithelialization; and (iv) a surprising increase in wound site angiogenesis [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, it did lead to an earlier macrophage (MP) influx in both FIX-and FVIIa-treated HB animals compared with untreated HB mice. Thus, it appears that two major mechanisms operate to promote MP influx to a wound site: (i) thrombin plays an important role in promoting rapid MP influx in wild type (WT) mice; and (ii) haemorrhage promotes MP influx into the wound area in HB mice [31]. The pattern of MP influx in the treated HB mice is a composite of the pattern seen in WT and HB mice: an early influx of MP is related to thrombin generation during haemostasis and a late influx of MP occurs in response to recurrent haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…With repeated bleeding, there is deposition of iron in synovial membrane. However the iron deposits are not physiologically functional as they are not readily available for haemoglobin synthesis but rather are pathological mediators of inflammatory changes leading to crippling synovitis and arthropathy [14].…”
Section: Discussionmentioning
confidence: 99%